Economic management methodology of rail transport innovation-oriented development - D. A. Macheret; A. V. Kudryavtseva (Вестник Научно-исследовательского института железнодорожного транспорта)
To ensure the strategic competitiveness of the rail-development of rail transport should be based on an adequate way industry, its long-term development must be innovative-ori-economic methodology, the development of which is an urgent ented. The economic toolkit for managing innovation-oriented scientific task. The article considers methodological approaches to the management of innovation-oriented development. Based on the synthesis of these approaches, a methodology is proposed for selecting promising innovative projects and solutions, taking into account both socio-economic and sectoral measurements. It is noted that for the success of innovative developments it is necessary that they meet the social and economic challenges. It is explained that the presented methodology contains exclusively qualitative approaches to assessing the prospects of innovation, according to the principle of subjective value evaluation. The article gives examples and considers four variants of the results of the assessment of innovation prospects from socio-economic and industry positions. The necessity of proactive management of innovation-oriented development of railway transport is substantiated. The paper underlines the importance of analyzing the trends of innovative development of other sectors of the economics (first of all - other modes of transport) under the proactive management of innovation-oriented development. The possibility of using the proposed methodology for selecting promising innovative projects and solutions can be noted in the context of proactive management of innovation-oriented development of rail transport, taking into account the necessary “tuning”.